Protective Effect of Polyoxometalates in Mo132/Maghemite Binary Superlattices Under Annealing - Breitwieser, Romain; Garnier, Adrien; Auvray, Thomas; Ngo, Anh-Tu; Baptiste, Benoit; Menguy, Nicolas; Proust, Anna; Petit, Christophe; Volatron, Florence; Salzemann, Caroline (Frontiers in Chemistry, 2019)
The binary assembly DDA-Mo132 / OA-γ-Fe2O3 (DDA=didodecyldimethylammonium, Mo132=[Mo132O372(CH3COO)30(H2O)72]42-, OA = oleic acid) constitutes one of the two examples in the literature of binary superlattices made of a mixing of nanocrystals and oxo-clusters. In a precedent work, we reported in details the preparation of such magnetic binary systems and studied the effect of the nature of the polyoxometalates (POMs) on the magnetic properties. In the present paper, we study the stability of this model binary assembly under heating at various temperatures. Indeed, especially if magnetic and/or transport properties are targeted, an annealing can be essential to change the phase of the nanocrystals in a more magnetic one and/or to desorb the organic capping of the nano-objects that can constitute an obstacle to the electronic communication between the nano-objects. The binary assembly showed a good stability at temperatures until around 400°C under vacuum thanks to the presence of the POMs that permits to avoid the aggregation of the nanocrystals as well as preserve their periodical arrangement. On the contrary, an assembly made of pure γ-Fe2O3 nanocrystals displays a clear aggregation of the nano-objects from 370°C, as attested by transmission and scanning electronic microscopies and confirmed by magnetic measurements. The stability of such POMs/nanocrystals assemblies opens the way to (i) the elaboration of new binary assemblies from POMs and numerous kinds of nanocrystals with a good control on the magnetic properties and to (ii) the investigation of new physical properties as exchange coupling, or magneto-transport in such systems.